Strategi Pembelajaran PAI dalam Meningkatkan Kemampuan Berpikir Kritis Kelas X di MA NU Putri Buntet Pesantren - Ahmad Bayanillah; Iis Arifudin; Yoyoh Badriyyah (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2026)
Critical thinking is an essential twenty-first-century skill that needs to be developed in Islamic Religious Education learning so that students are able to understand, analyze, and relate Islamic values to everyday life. In the context of MANU Putri Buntet Pesantren Cirebon, Islamic Religious Education has strong potential because it is supported by pesantren traditions such as musyawarah, syawir, and religious habituation; however, its implementation still faces challenges, including the dominance of lecture-based methods and students’ limited confidence in expressing opinions. This study aims to describe Islamic Religious Education learning strategies in improving the critical thinking skills of tenth-grade students at MANU Putri Buntet Pesantren Cirebon. This research employed a qualitative approach with a case study design. Data were collected through observation, semi-structured interviews, and documentation, then analyzed through data condensation, data display, and conclusion drawing. The findings show that Hiwar, Inquiry, and Discovery Learning strategies effectively encourage students to engage in dialogue, analyze religious issues, evaluate arguments, and reflect on Islamic values contextually. The main supporting factor is the pesantren culture of deliberation, while the inhibiting factors include the dominance of lecture-based learning, limited teacher time, and students’ suboptimal digital literacy. This study concludes that HOTS-based Islamic Religious Education learning can improve students’ critical thinking skills when implemented in a participatory, dialogical, and contextual manner in harmony with pesantren values